Revision of the orb-weaving spider genus Yaginumia Archer, 1960 (Araneae, Araneidae) from China - Xiaoqi Mi; Cheng Wang; Ming Su (ZooKeys)
The orb-weaver spider genus Yaginumia Archer, 1960 from China is revised, and three species, including two new species, are recognized: Y. medog Mi & Wang, sp. nov. (♂♀) from Xizang and Y. qiong Mi & Wang, sp. nov. (♂♀) from Hainan; the type species, Y. sia (Strand, 1906) (♂♀), is redescribed based on specimens from Guizhou and Hubei. A distributional map of the studied specimens is also provided.